Remuneraciones según actividades económicas y nivel educativo de los trabajadores en el sector privado del distrito de Iquitos, 2014 – 2022 - Huamán Freitas, Amanda Loreta (2025)
The general objective of this research was to determine the relationship between remuneration according to economic activities and educational level of workers in the private sector of the district of Iquitos from 2014 to 2022. For which the following methodology was taken into account, it was quantitative type, non-experimental design since its variables did not undergo manipulations and its type of design was longitudinal since it was taken over a time interval of 9 years, from 2014 to 2022, with a correlational level, because the correlation was measured in statistical terms. Obtaining an excellent correlation between remuneration according to economic activities with the educational level of Professional Title due to the following results: Correlation coefficient: r = 0.911589124 and the Coefficient of determination or R2 = 0.83099473 which are between 0.80 and 0.90 (-0.9 < r < -0.8), while for the other educational levels of Primary, Secondary, Higher Institute, University and Baccalaureate there was no correlation because their values for r were less than 0.30 and greater than -0.3, except for the educational level of Technical where there was a minimum correlation, the Correlation Coefficient being: r = -0.555994099 and the Determination Coefficient or R2 = 0.309129438, being between 0.30 and 0.60 (-0.6 < r < -0.3). Furthermore, both variables, both Economic Activities and Educational Level in terms of remuneration, presented a very changing behavior, due to various external factors.